Investigating the effect of noise exposure on mental disorders and the work ability index among industrial workers. (January 2022) - Monazzam Esmaielpour, Mohammad R; Zakerian, Seyed A; Abbasi, Milad; Ábbasi Balochkhaneh, Faezeh; Mousavi Kordmiri, Seyed Hojat
Noise as one of the most common hazardous physical agents in the work environment causes physical and psychological problems in occupied workers. This study aims to investigate the relationship of demographic variables and noise exposure with mental disorder and work ability index in automotive industry workers. This study aims to investigate the effect of noise exposure on mental disorder and work ability index among industry workers. In this descriptive-analytic study, 325 individuals working in auto parts supplier industry who were exposed to different level of noises were investigated. Personnel's daily exposure to noise for each group was measured based on ISO-9612 standards using calibrated sound level meter model SVANTEK-971. Workers' mental disorder and work ability index were determined using Kessler Psychological Distress Scale questionnaire and shortened form of work ability index, respectively. Then, collected data were analyzed using SPSS-22. The mean and standard deviation of mental disorder and work ability index for all employees was 23.46 ± 3.45 and 37.43 ± 6.14, respectively. The results of one-way ANOVA and linear regression analysis showed that there is a significant association between noise exposure with mental disorder and work ability index in term of age groups, working groups, and work experience ( p -value < .05). Regardless the effect of other variables, it can be stated that for each dB increase in noise exposure cause mental disorder increase by 0.32 and work ability index decrease by 0.157. And among the demographic variables, age was the most influential parameter on mental health and work ability index. According to the results of this study, noise exposure could lead to increased psychological distress and decreased work ability index in workers. The ability to work directly and indirectly through mental disorders can be affected by exposure to industrial noise. Considering severe exposure to noise in some units and the negative impact of noise exposure on mental health and work ability index, it is necessary to improve of controlling and protective measures against noise.